Hydrothermal liquefaction process of Ammi visnaga and a new approach for recycling of the waste process water: cultivation of algae and fungi - Durak, Halil; Genel, Salih; Durak, Emre Demirer; Ozcimen, Didem; Kocer, Anil Tevfik (SPRINGER HEIDELBERG, 2024)
In this study, biomass was tried to be liquefied by catalytic hydrothermal process. In addition, the effects of waste process water on growth of beneficial-pathogenic fungi and algae were investigated. Ammi visnaga as biomass source; Cu, W, and Fe metal powders as catalysts; Trichoderma harzianum, Trichoderma vixens, and Verticillium dahliae as fungus species; and Chlorella minutissima as algae were used. In trials, 250, 275, 300, and 325 degrees C temperatures and 0, 15, 30, and 45 min parameters were determined. GC-MS, TOC, XRD, and elemental analysis methods were used for characterization. The optimum temperatures for light bio-oil and heavy bio-oil were 300 degrees C and 325 degrees C, respectively. The highest HHV value was obtained as 30.30 Mj/kg in the presence of Fe catalyst. It was determined that waste process waters support beneficial fungus and algae growth and suppress pathogen growth.
Keywords: Hydrothermal liquefaction; Bio-oil; Catalyst; Algae; Fungi; CHLORELLA-MINUTISSIMA; BIOMASS; CONVERSION; BIODIESEL; YIELD; FE; Energy & Fuels; Engineering